2015
DOI: 10.1038/ncomms7999
|View full text |Cite
|
Sign up to set email alerts
|

Chip-based analysis of exosomal mRNA mediating drug resistance in glioblastoma

Abstract: Real-time monitoring of drug efficacy in glioblastoma multiforme (GBM) is a major clinical problem as serial re-biopsy of primary tumors is often not a clinical option. MGMT (O6-alkylguanine DNA alkyltransferase) and APNG (alkylpurine-DNA-N-glycosylase) are key enzymes capable of repairing temozolomide-induced DNA damages and their levels in tissue are inversely related to treatment efficacy. Yet, serial clinical analysis remains difficult and when done, primarily relies on promoter methylation studies of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
516
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 529 publications
(526 citation statements)
references
References 35 publications
7
516
0
3
Order By: Relevance
“…MGMT counteracts TMZ effects by direct removal of the O6-methyl group from alkylated guanines [81]. Interestingly, it was reported that GBM EVs from cell lines resistant to TMZ as well as from treatment-refractory patients carry elevated levels of MGMT mRNA, and that these levels are predictive for patient outcome [82]. We therefore do not exclude that EV transfer of MGMT mRNA molecules facilitates, at least partly, the resistance to TMZ observed [6063].…”
Section: Discussionmentioning
confidence: 99%
“…MGMT counteracts TMZ effects by direct removal of the O6-methyl group from alkylated guanines [81]. Interestingly, it was reported that GBM EVs from cell lines resistant to TMZ as well as from treatment-refractory patients carry elevated levels of MGMT mRNA, and that these levels are predictive for patient outcome [82]. We therefore do not exclude that EV transfer of MGMT mRNA molecules facilitates, at least partly, the resistance to TMZ observed [6063].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of the DNA repair enzymes APNG and MGMT are inversely correlated to response to the gold standard chemotherapeutic temozolomide 30 . EVs containing MGMT mRNA have been demonstrated to accurately reflect the levels of these enzymes in parental cells and in patients throughout treatment and therefore could serve as a potential 'real-time' biomarker of chemotherapy response during drug treatment 70 . Similarly, circulating EVs containing the EGFRvIII splice variant that is thought to be predictive of response to EGFR inhibition were detectable in the serum of GBM patients but not in the 30 matched controls 71 .…”
Section: Evs As 'Real-time' Biomarkers During Cancer Therapiesmentioning
confidence: 99%
“…51 In addition, as mentioned above, MGMT methylation status in circulating EVs was also found to correspond with the identity of the parental tumor and be predictive of the current response to treatment. 52 Altogether, this recent series of studies hold promise that EVs content may provide a novel tool for early diagnosis and companion biomarkers in combination with the current methods. 10,48 Could EVs be functionally targeted?…”
Section: Translational Outcomes and Clinical Potentialmentioning
confidence: 96%